20-Hydroxyecdysone prevents oxidative stress damage in adult Pyrrhocoris apterus - Krishnan, Natraj; Vecera, Josef; Kodrík, Dalibor; Sehnal, Frantisek (Archives of insect biochemistry and physiology, 2007)
Injections of 38 pmol paraquat (1,1'-dimethyl-4,4'-bypyridilium) into adult Pyrrhocoris apterus (average body weight 29.6 mg in males and 36.9 mg in females) caused a significant elevation of lipid peroxidation and protein carbonylation and a decline of membrane fluidity in the microsomal brain fraction. Another manifestation of oxidative stress was a depletion of the reduced glutathione pool and reduction of the gamma-glutamyl transpeptidase activity in the brain extracts. The damaging action of paraquat on the brain was counteracted by simultaneous injection of 1 pmol 20-hydroxyecdysone (20E). 20E restrained lipid peroxidation and the formation of protein carbonyls, ameliorated changes in microsomal membrane fluidity, enhanced the level of reduced glutathione, and upregulated the activity of gamma-glutamyl transpeptidase. At the organismic level, 20E curtailed three detrimental effects caused by paraquat injection: the disappearance of a blood protein, the suppression of fecundity and egg hatchability, and the shortening of adult life span. The data showed that 20E provided a systemic antioxidant protection but the significance of endogenous ecdysteroids in the management of oxidative stress remains to be shown.
Keywords: gama-glutamyltransferasa; Oxidative Stress; Ecdysterone; oxidační stres; hmyzí proteiny; Female; gamma-Glutamyltransferase; Biomarkers; zvířata; Glutathione; paraquat; biologické markery; ženské pohlaví; Male; Hemolymph; Sex Characteristics; herbicidy; glutathion; Heteroptera; pohlavní dimorfismus; Herbicides; Animals; Paraquat; ekdysteron; mužské pohlaví; hemolymfa; Insect Proteins